Teologi Inkarnasi Sebagai Landasan Praksis Pembentukan Perilaku Sosial Masyarakat - Hironimus Resi; Teresia Noiman Derung (IAKN Ambon, 2022)
The theology of the incarnation is the embodiment of God's highest love for man as the redeemer of man. The event of the incarnation became a very real sign of God's love in all human life that was in line with Him